2021
DOI: 10.1007/s11356-021-15940-w
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of arsenic, cadmium and lead in two artisanal and small-scale gold mining areas in Zimbabwe

Abstract: People living and working in artisanal and small-scale gold mining (ASGM) areas are frequently exposed to elemental mercury (Hg), which is used for gold extraction. However, additional exposure to other toxic metals such as arsenic (As), cadmium (Cd) and lead (Pb) may result from mining-related activities and could be ingested via dust, water or food. In these areas, only limited biomonitoring data is available for toxic metals other than Hg. In particular, data about the exposure to As, Cd and Pb is unavailab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…The mean value of As in the urine sample was 42.04 µg/L, with a range of 10.00 to 82.00 µg/L. The result in the present study for urinary As levels were higher than the studies from mining areas in Zimbabwe 41 and Guatemala. 42 Urinary As levels in Michigan urban anglers were found lower than the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…The mean value of As in the urine sample was 42.04 µg/L, with a range of 10.00 to 82.00 µg/L. The result in the present study for urinary As levels were higher than the studies from mining areas in Zimbabwe 41 and Guatemala. 42 Urinary As levels in Michigan urban anglers were found lower than the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…People living and working in both artisanal and gold-mining areas are frequently exposed to Hg, which is used for gold extraction. It is estimated that about 15 million miners are affected globally [ 56 ]. Additionally, exposure to other toxic metals such as arsenic (As), Pb, Cd, and Mn may occur through mining-related activities and could be ingested via air, sediment, water, or food contamination [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mining activities such as excavation, crushing, and milling may result in the increased liberation of these toxic metals. Although the gold metal is collected at the end of the mining process, metals may end up in the tailing dumps at mining locations, thus presenting an exposure hazard for people living and working in these mining areas [ 56 ]. Santos et al (2020) found that surface-sediment samples collected in an area under the influence of gold mining were polluted (moderately to seriously) [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soil from all parts of the study area still exceeds the German precautionary value of 70 mg lead per kg soil (Landkreis Goslar 2017 ). Other similarly polluted regions show comparable lead levels in their population (Schoof et al 2016 ; Rakete et al 2022 ). Other studies, for example, in Kabwe (Zambia), which has lead levels in soil ranging from 139 to 62,142 mg/kg, children’s lead blood values were approximately 30 times as high as the ones measured in the present study (Bose-O'Reilly et al 2018 ).…”
Section: Discussionmentioning
confidence: 89%